Implementasi Permainan Tradisional Engklek dalam Pengenalan Konsep Bangun Datar melalui Pendekatan Etnomatematika Pada Anak-Anak - Anatasya Setiasih; Achmad Apriza; Lilia Gina Febrila (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Traditional games are part of cultural heritage that possess educational value and can be utilized as learning media. One of the traditional games still recognized by the community is Engklek. This game not only serves as a form of entertainment but also contains various mathematical concepts that can be studied through an ethnomathematical approach. This study aims to describe the implementation of ethnomathematics in the traditional game of Engklek and to identify the mathematical concepts embedded within it as a learning medium for children. This research employed a descriptive qualitative approach with children living on Padang Makmur 2 Street, Bumi Ayu, Selebar District, as the research subjects. Data were collected through observation, interviews, and documentation. The collected data were analyzed using data reduction, data presentation, and conclusion drawing techniques. The results showed that the Engklek game contains various mathematical concepts, including plane geometry, patterns, number sequences, position, and distance measurement. These concepts are reflected in the design of the game board and the rules applied during play. Through Engklek, children can learn geometric concepts in a more concrete and enjoyable way. In addition, the game helps improve children's activeness, logical thinking skills, and interest in learning mathematics. Therefore, the traditional Engklek game can be used as an effective ethnomathematics-based learning medium to support students' understanding of mathematical concepts while also contributing to the preservation of local cultural heritage in the modern era.